2011
DOI: 10.1002/eji.201040528
|View full text |Cite
|
Sign up to set email alerts
|

CD6 attenuates early and late signaling events, setting thresholds for T‐cell activation

Abstract: The T lineage glycoprotein CD6 is generally considered to be a costimulator of T-cell activation. Here, we demonstrate that CD6 significantly reduces early and late T-cell responses upon superantigen stimulation or TCR triggering by Abs. Measuring calcium mobilization in single cells responding to superantigen, we found that human T cells expressing rat CD6 react significantly less well compared with T cells not expressing the exogenous receptor. When the cytoplasmic domain of rat CD6 was removed, calcium resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 44 publications
8
72
0
Order By: Relevance
“…For an example, tumor suppressor gene RBP1 is a regulator of breast epithelial retinoic acid recepter activity, cell differentiation, growth arrest and cell cycle progression [9], [10], and it was identified as a driver genes with promoter hypermethylation disturbing "cell cycle". As another example, CD6 was identified as a driver genes with promoter hypomethylation, in accordance with previous report that increased expression of CD6 suppresses longer term events such as cytokine secretion and T-cell proliferation [11], which could promoter the initiation of cancer. Secondly, in addition to the known cancer genes collected in the F-census database, some driver genes have been suggested to be cancer genes in previous studies.…”
Section: B Validation Of the Identified Driver Genessupporting
confidence: 88%
“…For an example, tumor suppressor gene RBP1 is a regulator of breast epithelial retinoic acid recepter activity, cell differentiation, growth arrest and cell cycle progression [9], [10], and it was identified as a driver genes with promoter hypermethylation disturbing "cell cycle". As another example, CD6 was identified as a driver genes with promoter hypomethylation, in accordance with previous report that increased expression of CD6 suppresses longer term events such as cytokine secretion and T-cell proliferation [11], which could promoter the initiation of cancer. Secondly, in addition to the known cancer genes collected in the F-census database, some driver genes have been suggested to be cancer genes in previous studies.…”
Section: B Validation Of the Identified Driver Genessupporting
confidence: 88%
“…Thus, while the T cell‐activating properties of CD6 depend upon binding to CD166, its inhibitory effects have been shown to be independent of the interaction with this ligand. Furthermore, ligand‐dependent localization of CD6 at the synapse region is not required for the inhibitory functions, whereas it is required for the T cell‐activating functions of CD6 .…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies using mAbs to CD6 have demonstrated its role in T cell activation, proliferation [27]–[30] and in regulating the expression of intracellular phosphoproteins and production of proinflammatory cytokines [31]. Furthermore, CD6 is involved in the maturation of the immunological synapse (IS) by associating at the central supramolecular activation cluster (cSMAC) region [25].…”
Section: Introductionmentioning
confidence: 99%